2020
DOI: 10.1021/acsapm.9b01089
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine-Based Mechano-Fluorochromic Gels and Solids: Superhydrophobic Surface Formation and Crystal-to-Crystal Phase Transition

Abstract: Organic materials exhibiting mechano-fluorochromic behavior in their gel state are extremely rare in the literature. Similarly, examples of mechano-fluorochromic organic materials with crystal-to-crystal phase transitions have not been reported until date. Herein, we achieved these two remarkable properties in phenothiazine derivatives S1 and S2[(E)-N′-((10-ethyl-10H-phenothiazin-3-yl)­methylene)-3,4,5-tris­(hexadecyloxy)­benzohydrazide and (E)-N′-((10-ethyl-10H-phenothiazin-3-yl)­methylene)­isonicotinohydrazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…According to the above-mentioned statement, the aggregation-induced redshift in emission is attributed to the unrestricted rotation in the aggregation state of the BTBT derivatives. 30 Closer inspection of the emission spectra revealed that the compound in DMSO covered most of the visible region, which may guide single molecular white light emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the above-mentioned statement, the aggregation-induced redshift in emission is attributed to the unrestricted rotation in the aggregation state of the BTBT derivatives. 30 Closer inspection of the emission spectra revealed that the compound in DMSO covered most of the visible region, which may guide single molecular white light emission.…”
Section: Resultsmentioning
confidence: 99%
“…According to the above-mentioned statement, the aggregationinduced redshift in emission is attributed to the unrestricted rotation in the aggregation state of the BTBT derivatives. 30 Closer inspection of the emission spectra revealed that the compound in DMSO covered most of the visible region, which may guide single molecular white light emission. The solid-state PL emission was investigated using different percentage loadings of the compounds, namely 25%, 50%, 75% and 100%, and it was observed that an increase in the percentage loading caused an increase in emission intensity (Fig.…”
Section: Pccp Papermentioning
confidence: 99%
“…57 The observation also shows an aggregation-induced unusual blue-shift in PT-C2-(Nap) 2 and PT-C12-(Nap) 2 , which might be due to the inhibition TICT in the aggregated state of the naphthyl derivatives. 58 In general, the AIE effect leading to a blue shift are relatively less compared to those which exhibit a red shift upon aggregation. Among PT-C2-(An) 2 , PT-C2-(Pn) 2 and PT-C2-(Pr) 2 (Fig.…”
Section: Paper Materials Advancesmentioning
confidence: 99%
“…Furthermore, it has been seen that upon grinding, the fluorescence lifetime of the ground sample has been enhanced. This can be attributed to the improved interaction between phenothiazine (PT) phenyl (Ph) and PT-long alkyl chain noncovalent interactions 58 (viz. p-p, C-HÁ Á Áp and C-HÁ Á ÁH-C) (Fig.…”
Section: Materials Advances Papermentioning
confidence: 99%
See 1 more Smart Citation